2012
DOI: 10.1016/j.virol.2012.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Deep Sequencing of HIV-1 Reverse Transcriptase Before Start of an NNRTI-based Regimen in Treatment-naive Patients

Abstract: There are conflicting data on the impact of low frequency HIV-1 drug-resistant mutants on the response of first-line highly active antiretroviral therapy (HAART), more specifically containing a NNRTI. As population sequencing does not detect resistant viruses representing less than 15-25% of the viral population, more sensitive techniques have been developed but still need clinical validation. We evaluated ultra-deep sequencing (UDPS), recently more available and affordable, as a tool for the detection of HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…Nonetheless, using a deep sequencing-based HIV-1 genotyping assay (DEEPGEN) [43] we were able to identify low-level HIV-1 variants (at a frequency of <20% of the population) carrying 59 additional drug-resistance mutations in the protease, reverse transcriptase and integrase coding regions of viruses from these highly antiretroviral-experienced patients. Previous studies have described similar findings, although analyzing no more than one or two drug-targeted regions at a time, in antiretroviral-naïve [65], [66], [73], [74], [75], [76] or -experienced HIV-infected individuals [43], [68], [69], [77], [78], [79], [80], with the detection of minority mutations usually correlating with historical antiretroviral treatment. In the case of INSTI-resistance mutations, using deep sequencing we corroborated and quantified all the amino acid substitutions identified by Sanger sequencing, even in positions labeled as mixtures, e.g., E92E/Q (55.1% E92Q) or N155N/H (79.9% N155H) in patients 08–172 and 08–177, respectively.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Nonetheless, using a deep sequencing-based HIV-1 genotyping assay (DEEPGEN) [43] we were able to identify low-level HIV-1 variants (at a frequency of <20% of the population) carrying 59 additional drug-resistance mutations in the protease, reverse transcriptase and integrase coding regions of viruses from these highly antiretroviral-experienced patients. Previous studies have described similar findings, although analyzing no more than one or two drug-targeted regions at a time, in antiretroviral-naïve [65], [66], [73], [74], [75], [76] or -experienced HIV-infected individuals [43], [68], [69], [77], [78], [79], [80], with the detection of minority mutations usually correlating with historical antiretroviral treatment. In the case of INSTI-resistance mutations, using deep sequencing we corroborated and quantified all the amino acid substitutions identified by Sanger sequencing, even in positions labeled as mixtures, e.g., E92E/Q (55.1% E92Q) or N155N/H (79.9% N155H) in patients 08–172 and 08–177, respectively.…”
Section: Discussionsupporting
confidence: 64%
“…While a few studies have failed to establish an association between the presence of minority variants carrying drug resistance mutations and therapeutic failure [66], [67], [68], [69], many others have associated the identification of low-abundance drug-resistant viral variants as having an impact in treatment outcome [32], [35], [44], [45], [65], [70]. It is possible that the threshold for the identification of significant low-level variants may be mutation and/or antiretroviral drug dependent [31]; thus, it is clear that additional studies based on reliable ultrasensitive assays are needed to better understand the clinical relevance of these minority HIV-1 variants.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, low-frequency mutations may emerge in patients with inadequate treatment management [49,50,51]. Recently, NGS sequencing has been proposed as an alternative to sequencing-based methods to identify mutations associated with resistance to antiretrovirals [52,53]. The NGS-based HIV assay is a new platform that allows the monitoring of low abundance viral variants.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was also demonstrated that these low-abundance mutations can have a significant impact on virological failure, mostly for non-nucleoside analog RT inhibitor (NNRTI) mutations (6,(15)(16)(17)(18). However, despite its high accuracy and effectiveness, the GS FLX platform exceeds the capacity of smalland medium-scale projects, limiting its application for routine testing.…”
mentioning
confidence: 99%